2003
DOI: 10.1111/j.1740-8261.2003.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Polyp in the Middle Ear With Secondary Suppurative Meningoencephalitis in a Cat

Abstract: Nasopharyngeal polyps are non-neoplastic masses, originating from the mucosa of the nasopharynx, the tympanic bulla or the Eustachian tube. Inflammatory polyps extending into the tympanic bulla cavity are a common cause of otitis media in cats. In dogs, however, occurrence of middle ear polyps has rarely been reported. The present report describes the findings of the clinical examination, diagnostic imaging and histopathological appraisal of a ten year old male dog with an inflammatory middle ear polyp arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
2
16
0
3
Order By: Relevance
“…Several cats with rhinitis had concurrent nasopharyngeal conditions that were believed to have contributed to, or developed as a result of chronic rhinitis including: inflammatory polyps, acquired nasopharyngeal stricture or cicatrix formation, mucosal hyperplasia, and lymphoid follicular hyperplasia. These conditions have been associated with chronic nasal or nasopharyngeal inflammation in cats, dogs, and humans and may be mistaken for neoplasia on gross examination 17,24–29 . Inflammatory polyps were considered the source of rhinitis in one cat (1.5 years of age) and chronic rhinitis was considered contributory to polyp formation in two cats (5.5 and 10 years of age, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Several cats with rhinitis had concurrent nasopharyngeal conditions that were believed to have contributed to, or developed as a result of chronic rhinitis including: inflammatory polyps, acquired nasopharyngeal stricture or cicatrix formation, mucosal hyperplasia, and lymphoid follicular hyperplasia. These conditions have been associated with chronic nasal or nasopharyngeal inflammation in cats, dogs, and humans and may be mistaken for neoplasia on gross examination 17,24–29 . Inflammatory polyps were considered the source of rhinitis in one cat (1.5 years of age) and chronic rhinitis was considered contributory to polyp formation in two cats (5.5 and 10 years of age, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…87 Diagnosis via otoscopy may be possible if the tympanic membrane is irregular, bulging or ruptured. Clinical signs may progress to otitis interna or otitis externa, facial nerve paralysis, laryngeal paralysis, Horner's syndrome, keratoconjunctivitis sicca, and exposure keratitis, and may rarely extend into the pharynx.…”
Section: Neoplasiamentioning
confidence: 99%
“…In 10 cats for which the outcome was reported, 2/10 (20%) recovered with no residual neurologic deficits, 2/ 10 (20%) recovered with persistent neurologic deficits, 4/ 10 (40%) were euthanized because of clinical deterioration, and 2/10 (20%) died. 6,[11][12][13][14][15][16][17] The high mortality associated with bacterial CNS infections is because of the difficulty of diagnosing the disease, which results in delayed or inappropriate therapy. One recent study of cats with inflammatory CNS disease found that an antemortem diagnosis could not be made in 18/62 (29%) cases.…”
mentioning
confidence: 99%
“…19,20 In a literature review of feline CSF bacterial culture, antemortem CSF cultures were attempted in 2/ 15 cats and positive in 1/2 cats with CNS disease. 12,14 Several factors likely contribute to poor culture performance in veterinary medicine. Only small volumes of CSF are collected for culture, the organisms are in the brain parenchyma and thus are present in the CSF in small numbers, some organisms are slow growing or require nonstandard culture techniques, and animals often receive antibiotic therapy before sampling.…”
mentioning
confidence: 99%
See 1 more Smart Citation